Artesunate and chloroquine induce cytotoxic activity on cholangiocarcinoma cells via different cell death mechanisms - Guragain, Diwakar; Seubwai, Wunchana; Kobayashi, Daiki; Silsinivanit, Atit; Vaeteewoottacharn, Kulthida; Sawanyawisuth, Kanlayanee; Wongkham, Chaisiri; Wongkham, Sopit; Araki, Norie; Cha'on, Ubon (Cellular and Molecular Biology, 2018)
Chemotherapy for cholangiocarcinoma (CCA) is not quite successful. In this study, we revisited the possibility of artesunate (ART) and chloroquine (CQ), the antimalarial drugs, as therapeutic agents against CCA. The possible mechanisms of these drugs to exert cytotoxicity on CCA cells were also explored. The effects of ART and CQ on proliferation and death patterns of two CCA cell lines, KKU-214 and its highly metastatic subtype KKU-214L5, were examined using water soluble tetrazolium (WST) assay and time-lapse photometry, respectively. To differentiate and verify the death patterns between necrosis and apoptosis, lactate dehydrogenase (LDH) release, and caspase 3 activity were measured. CellROXTM green reagent staining method was used to assess reactive oxygen species (ROS) production in ART- and CQ-treated cells. ART and CQ significantly inhibited proliferation of CCA cells. Both drugs kill malarial parasites via similar mechanism depending on ROS formation, however, ART induced necrotic cell death and CQ induced apoptotic cell death in CCA cells. ART induced LDH release, whereas CQ activated caspase 3, confirming induction of necrotic and apoptotic cell deaths by ART and CQ, respectively. ART treatment induced higher ROS production than CQ. ART and CQ induce CCA cells death via different death pathways. ART should be suitable for necrosis-sensitive CCA, whereas CQ is more suitable for apoptosis-sensitive CCA.